JUDICIAL ANTI-CORRUPTION CAMPAIGNS prosecutions in italy, brazil and romania. - HOGIC, NEDIM (ROUTLEDGE, 2025)
This book offers a comparative analysis of cases of mass prosecutions for political corruption in Italy, Brazil, and Romania.The book outlines how judicial showdowns with political corruption emerge, what consequences they create, and whether they can be considered legitimate judicial operations or coups orchestrated by political forces with the assistance of the judiciary. Due to the similarities exhibited in the legal, political, and economic spheres of the events, the book explores the Italian Mani Pulite, Brazilian Lava Jato, and Romanian judicial anti-corruption campaigns. These campaigns were simultaneously legal operations, narratives created by the media, and opportunities for the emergence of new political actors. The book demonstrates why judicial activity was a crucial tool for reducing and preventing corruption in these countries. In addition to investigating the key legal issues and narratives, the book explores the controversies of these campaigns and assesses whether they should be seen as judicial revolutions or cases of prosecutorial overreach.Providing a holistic comparative assessment of judicial means as a tool for controlling corruption, this book will be of interest to academics in the fields of Corruption Studies, Law, Development Studies, and Political Science.
Keywords: Political corruption -- Law and legislation -- Italy.; Political corruption -- Law and legislation -- Brazil.; Political corruption -- Law and legislation -- Romania.; Political corruption -- Law and legislation -- Italy -- Case studies.; Political corruption -- Law and legislation -- Brazil -- Case studies.; Political corruption -- Law and legislation -- Romania -- Case studies.; elektronické knihy; electronic books